Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/1938640013509670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Ankle Instability in High School and Division I Athletes

Abstract: Findings of this study revealed differences in the distribution of chronic ankle instability that warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 43 publications
6
102
5
1
Order By: Relevance
“…In a recent systematic review of the prevalence of CAI in sporting populations, Attenborough et al 115 indicated that CAI is a highly prevalent condition (>25%) in sports such as handball, basketball, soccer and volleyball. This has been confirmed in recent investigations of collegiate and high school athletes in which the prevalence of CAI was ∼25% in those athletes with a previous history of injury 116 117. Within the performing arts population, such as ballet, more than 50% of the dancers with a history of ankle sprain report CAI 118.…”
Section: Section B: Mid-term and Long-term Consequences Of Lassmentioning
confidence: 53%
See 1 more Smart Citation
“…In a recent systematic review of the prevalence of CAI in sporting populations, Attenborough et al 115 indicated that CAI is a highly prevalent condition (>25%) in sports such as handball, basketball, soccer and volleyball. This has been confirmed in recent investigations of collegiate and high school athletes in which the prevalence of CAI was ∼25% in those athletes with a previous history of injury 116 117. Within the performing arts population, such as ballet, more than 50% of the dancers with a history of ankle sprain report CAI 118.…”
Section: Section B: Mid-term and Long-term Consequences Of Lassmentioning
confidence: 53%
“…These trends are higher in athletic populations (at least 1 of 3)115 117 and among dancers (1 out of 2) 118. When examining the trends within the general public, individuals with chronic ankle problems report increased modification of functional activity and reduced overall health compared with their non-injured counterparts in the community.…”
Section: Section B: Mid-term and Long-term Consequences Of Lassmentioning
confidence: 99%
“…1,2 Multiple definitions and models have been used to define CAI. 3,4 However, because of its multi-faceted and heterogeneous character, CAI has recently been defined by the International Ankle Consortium (IAC) as being a chronic condition including three major aspects: (1) a history of at least one significant ankle sprain, (2) a history of ankle joint 'giving way' and/or recurrent sprain, and/or 'feelings of instability', (3) a poor disability status according to specific questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…1 Chronic ankle instability is a complex injury caused by mechanical and functional insufficiencies, found after the resolution of an initial lateral ankle sprain, which can lead to repetitive sprains and instability of the ankle joint. 2 Typically, individuals with CAI report feelings of the ankle ''giving way'' during activity.…”
mentioning
confidence: 99%